Motive And Its Influence On The Major Character'sBehavior In Danielle Steel's Remembrance: Humanistic Psychological Approach - Rosita., Nanik (2004)
This study deals with the influence of motive in individual's behaviour. This study aims at identifying the relationship between the motive and the behavior. This study uses qualitative method. The primary data source is Danielle Steel's Remembrance. Whereas, the secondary data source taken from references of psychology books and literature books which are relevant to the topic of the study. Technique of collecting data is library research. The technique of analyzing data is descriptive. The outcome of the study shows that motive influences human's behavior. Generally, human's behavior is almost always motivated and motive is a goal of human's behavior. It shows that every person always strives to reach self-fulfillment. The problem appeared on the person shows that the major character is motivated to live a glamorous life in order to actualize herself to be a popular model.